2013
DOI: 10.1371/journal.pone.0054388
|View full text |Cite
|
Sign up to set email alerts
|

Lizard and Frog Prestin: Evolutionary Insight into Functional Changes

Abstract: The plasma membrane of mammalian cochlear outer hair cells contains prestin, a unique motor protein. Prestin is the fifth member of the solute carrier protein 26A family. Orthologs of prestin are also found in the ear of non-mammalian vertebrates such as zebrafish and chicken. However, these orthologs are electrogenic anion exchangers/transporters with no motor function. Amphibian and reptilian lineages represent phylogenic branches in the evolution of tetrapods and subsequent amniotes. Comparison of the pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…NLC and electromotility are fully coupled in mammalian OHCs [21, 23, 24] and the former could be evaluated accurately [1619]. Our NLC measurements show that, for apical OHCs, the function of prestin first appears at P9 and reached mature level at P14 (Figure 4).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…NLC and electromotility are fully coupled in mammalian OHCs [21, 23, 24] and the former could be evaluated accurately [1619]. Our NLC measurements show that, for apical OHCs, the function of prestin first appears at P9 and reached mature level at P14 (Figure 4).…”
Section: Discussionmentioning
confidence: 82%
“…Cells showing any signs of shrinkage, swelling, or damage were excluded from the patch-clamp recording. Nonlinear capacitance (NLC) was measured as described in our previous publications [1619]. The recording patch pipette was pulled by a pipette puller (P97, Sutter) and back-filled with the intracellular solution (140 CsCl, 10 EGTA, 2 MgCl 2 , and 10 HEPES in mM, 305 mOsm and pH 7.35).…”
Section: Methodsmentioning
confidence: 99%
“…Two other studied found that prestin can act as a weak Cl − /HCO3 − antiporter (Mistrik et al, 2012) or as a weak electrogenic anion transport (Schanzler and Fahlke, 2012). It is worth noting that recent studies using radioactive anion uptake techniques failed to detect anion uptakes in mammalian prestin (Tan et al, 2011; Tang et al, 2013). In spite of the fact that it is still controversial whether prestin retains transport function, it is quite certain that its transport capability is significantly diminished as prestin gains motor function in mammals during evolution (Tan et al, 2011; Schanzler and Fahlke, 2012).…”
Section: Molecular Mechanism Of How Prestin Workmentioning
confidence: 99%
“…Healthy young Sprague Dawley rats of either sex (21–28 days old, body weight 40–70 g) exhibiting normal hearing were used for the experiments. The CM measurements and whole-cell patch recordings were performed as previously described [26, 27]. These methods are briefly described as follows.…”
Section: Methodsmentioning
confidence: 99%